Initial public offerings 2 - Cooney, John (Henry Stewart Talks, 2015)
Underpricing: Rock (1986) model, Underpricing: investment bank certification, Underpricing: VC certification, Underpricing: partial adjustment phenomenon, Market imperfection: price stabilization, Market imperfection: the quiet period, Market imperfection: the lockup period, Analyst conflict of interest, Changing incentives of issuers and investment banks, Gross spreads, Informational content of the prospectus, Competitive effects of IPOs, Long-run returns
Reviewed at 2024/03/05